2011
DOI: 10.1111/j.1582-4934.2011.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental acute myocardial infarction: telocytes involvement in neo-angiogenesis

Abstract: We used rat experimental myocardial infarction to study the ultrastructural recovery, especially neo-angiogenesis in the infarction border zone. We were interested in the possible role(s) of telocytes (TCs), a novel type of interstitial cell very recently discovered in myocardim (see ). Electron microscopy, immunocytochemistry and analysis of several proangiogenic microRNAs provided evidence for TC involvement in neo-angiogenesis after myocardial infarction. Electron microscopy showed the close spatial associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(194 citation statements)
references
References 69 publications
7
182
0
5
Order By: Relevance
“…Reports have suggested that the myocardial tissue secretes exosomes, and exosomes and microvesicles could be an important mechanism involved in heterocellular communication in the adult heart, 78,79 especially exosomes emerging from telocytes in the border zone of MI. 79 Barile et al 78 provided ultrastructural evidence for the first time that exosomes and microvesicles are secreted by the progenitor cells in a normal adult mouse heart. They have also demonstrated a possible uptake of exosomes by cardiomyocytes in the adult mouse heart.…”
Section: Myocardium Secretes Exosomes: In Vivo Evidencementioning
confidence: 99%
“…Reports have suggested that the myocardial tissue secretes exosomes, and exosomes and microvesicles could be an important mechanism involved in heterocellular communication in the adult heart, 78,79 especially exosomes emerging from telocytes in the border zone of MI. 79 Barile et al 78 provided ultrastructural evidence for the first time that exosomes and microvesicles are secreted by the progenitor cells in a normal adult mouse heart. They have also demonstrated a possible uptake of exosomes by cardiomyocytes in the adult mouse heart.…”
Section: Myocardium Secretes Exosomes: In Vivo Evidencementioning
confidence: 99%
“…Rat experimental MI was investigated using electron microscopy, immunocytochemistry and analysis of several pro-angiogenic miRNAs that provided evidence for TC involvement in neo-angiogenesis after MI. TCs contain measurable quantities of angiogenic miRNAs (let- 7e, miR-10a, miR-21, miR-27b, miR-100, miR-126-3p, miR130a, miR-143, miR-155 and miR-503) [101] .…”
Section: Mesenchymal-stem Cells and Mirnasmentioning
confidence: 99%
“…TCs may be nurse cells, integrating local, short-distance signals (direct contacts, exosomes and shedding vesicles) and long-distance signals through the long TPs, due to their 3D network. Recent studies have demonstrated a particular immunophenotype (34,35), distinct microRNA expression (36), specific gene-expression profiles (37) and peculiar electrophysiological properties of TCs in various organs (38). Close contact between TCs and fibroblasts was indicated in the present study.…”
Section: Discussionmentioning
confidence: 52%